Understanding The Problems Of Early Marriage Perspective KH. Husein Muhammad And Their Relevance To Law No 16 Year 2019 Concerning Marriage - Shofiatul Jannah; Tutik Hamidah (Transformatif, 2022)
Early marriage is a timeless phenomenon, this case will always be interesting to be an object of research because in practice early marriage does not always lead to happiness, but instead leads to misery. Young men and women have not been able to manage emotions well, so early marriage partners often want to win on their own and cause arguments that will result in violence or even divorce. This research is a literature study with a qualitative type of research that is observing cases of early marriage that have occurred in Indonesia, especially how the law of early marriage in the perspective of positive law and Islamic law and its relevance to the thought of KH. Husein Muhammad as Indonesian Muslim feminist. The results of this study are the harmony between legal considerations in the law on the age limit for marriage and also the results of the study of KH. Husein Muhammad about early marriage. This means that the marriage law law and the study of Husein Muhammad are both concerned with the protection and safeguards so that there is no damage due to early marriage.